Konstruksi Maskulinitas dalam Lirik Lagu Pop Jawa Karya Denny Caknan - Ulya, Chafit; Hartono, Tirza Marshanda; Nur Annisa Laillatul Mila; Nur Samsiyah (Universitas Muhammadiyah Surakarta, 2025)
This study examines the construction of masculinity in the lyrics of Javanese pop songs by Denny Caknan using Janet Saltzman Chafetz’s seven dimensions of masculinity. Employing a qualitative descriptive method and content analysis, ten popular songs were selected through purposive sampling. The emotional dimension was the most dominant among the seven dimensions analyzed, followed by personal characteristics and interpersonal dimensions. This indicates that masculinity in Denny Caknan’s songs is primarily expressed through emotions, social relationships, and male personality traits. The intellectual and functional dimensions were moderately represented, suggesting that men in Javanese pop songs are also portrayed through their thoughts and actions in social life. Meanwhile, the physical and sexual dimensions were less prominent, indicating that physical strength and sexual identity are not the primary aspects of masculinity construction in Denny Caknan’s Javanese pop songs. This study contributes to gender studies by providing insights into how masculinity is constructed in contemporary Javanese pop music.